2001
DOI: 10.1051/0004-6361:20000302
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear obscuration and scattering in Seyfert 2 galaxies

Abstract: Abstract. We study the relation between gaseous absorbing column density (N H ), infrared colors and detectability of the broad lines in a large sample of Seyfert 2 galaxies(Sy2s). We confirm that Sy2s without polarized broad lines tend to have cooler 60µm/25µm colors; this correlation was previously ascribed to the effect of obscuration towards the nuclear region. We find some evidence that Sy2s without polarized broad lines have larger absorbing column density (N H ) and that a fraction of them are character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 29 publications
6
38
0
Order By: Relevance
“…This confirms the finding by several authors -also based on X-ray spectra -that non-HBLR and HBLR samples exhibit similar column densities and obscuration (e.g. Alexander 2001;Gu et al 2001;Tran 2003).…”
Section: Intrinsically Weak or Obscured Nucleisupporting
confidence: 91%
See 2 more Smart Citations
“…This confirms the finding by several authors -also based on X-ray spectra -that non-HBLR and HBLR samples exhibit similar column densities and obscuration (e.g. Alexander 2001;Gu et al 2001;Tran 2003).…”
Section: Intrinsically Weak or Obscured Nucleisupporting
confidence: 91%
“…There is no doubt that dust lanes may obscure not only the nucleus but also the scattering mirror necessary for the detection of a HBLR. Hence, only under favourable circumstances one may expect detectable scattered light at all from a hidden AGN (Miller & Goodrich 1990;Heisler et al 1997;Gu et al 2001). The AGN-typical emission line [OIII] λ5007 Å (henceforth denoted [OIII]) has an average equivalent width which is higher for HBLRs than for non-HBLRs, indicating a stronger AGN/host contrast in HBLRs (Lumsden et al 2001;Moran 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a smaller sample, Alexander (2001) argued that the absorbing column density N H of HBLR and non-HBLR S2 galaxies do not show any significant difference. Gu et al (2001), on the other hand, suggested that HBLR S2 galaxies may have on average smaller N H than non-HBLR S2 galaxies, using data available for a heterogeneous sample of HBLR S2 galaxies. For our larger and more complete sample, we show in Figure large uncertainties and thus may not reflect the true nature of the obscuration in S2 galaxies.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…Furthermore, there are also studies that separate Type I from Type II objects (e.g. Hunt et al 1997;Maiolino et al 1997;Gu et al 2001), implying that recent star formation is only present in Type II objects (see also Coldwell et al 2009). Based on the number and proximity of close ( 60-100 h −1 kpc) neighbours, around different types of active (Sy1, Sy2 and BIRG) galaxies (e.g.…”
Section: Discussionmentioning
confidence: 99%